Whole-genome sequencing reveals progressive versus stable myeloma precursor conditions as two distinct entities - Bénedith Oben (Nature Portfolio, 2021)
The factors that are associated with myeloma precursor condition progression are not well understood. Here the authors find that monoclonal gammopathies of undetermined significance and smoldering myelomas that did not progress to multiple myelomas have a distinct genomic profile and emerge later in the patient’s life.